Trade disruptions in Europe: Evidence from the EIB Investment Survey 2022 - Andrea Brasili; Peter Harasztosi (European Investment Bank (EIB), 2023)
Using firm level survey data we draw a portrait of incidence of recent trade related shocks, such as disruptions in logistics or access to materials, and undertaken responses in the economies of the EU. The paper focuses on firm heterogeneity in explaining the willingness to respond to these shocks and in explaining the type of response taken: diversification across trade partners or focusing on domestic markets and suppliers. We find that younger, larger, more productive firms are more likely to respond actively to trade shocks and disruptions, especially with diversification. At the same time, less productive, less innovative firms and firms using imported inputs, but that do not trade themselves are discouraged from engaging directly in international trade.
Keywords: D21; F1; L23; 330; international trade; firm heterogeneity; disruptions